The Impact of Taxation of the Domestic Economic Transactions on the Vat Collection Through Electronic Fiscal Devices - Ionel Bostan; Cristian Popescu; Costel Istrate; Ioan-Bogdan Robu (Amfiteatru Economic Journal, 2017)
The issue of collecting tax resources to the consolidated budget has determined and still determines difficulties which cannot be neglected in all the former socialist countries of the Central and Eastern Europe. From the Members States of the European Union, Romania is the country with the highest VAT Gap between EU Member States: 41%, compared to a European average of 15.2%. One solution tried to solve this problem was the regulation of mandatory use of electronic cash registers with fiscal memory. In this way, it was considered that a better highlight and also a tighter control of economic transactions will be achieved, from a fiscal point of view. In our study, we analyze, for the Romanian context in the post-EU accession, whether the mandatory introduction of these devices in recording commercial transactions has had a significant impact on VAT collection. The study includes two stages of the analysis: in the first stage we estimated the influence of VAT rate variation on the degree of the VAT collection. Then we used the residual component to test the influence of EFDs' mandatory introduction on VAT collection or on fiscal efficiency. The results indicate an improvement in the collection of VAT but also a decrease in the efficiency of fiscal collection.
Keywords: C58; E62; O33; 330; electronic fiscal devices; value added tax; fiscal efficiency; state/consolidated budget